Utilization of HDPE Plastic Waste for Asphalt Making Additives With A Combination of Glass Waste Filler - Amalia Ma’rifatul Maghfiroh; Alfia Nur Rahmawati (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
Asphalt is one of the materials used as a road pavement material, this material was chosen because of its good and comfortable final result as a flexible pavement. The use of HDPE plastic waste as an additive to asphalt material and glass waste as filler was chosen in making asphalt, because it is an effort to overcome the problem of waste and besides that the content contained in these materials is thought to be an alternative to making asphalt. The purpose of this study was conducted to determine the characteristics of the constituent materials of asphalt mixture with HDPE plastic additives and glass waste filler; Marshall characteristics of asphalt mixture with HDPE plastic additives and glass waste filler; and the optimum composition ratio to produce asphalt with HDPE plastic additives and glass waste filler. The research results of the effect of the addition of plastic (HDPE and glass powder, partial replacement of asphalt and partial replacement of filler with a mixture proportion of 10-15 mm Coarse Aggregate fraction with a composition of 10%, Medium Aggregate 5-10 mm 48%, Fine Aggregate 0-5 mm 38%%% included in the gradation envelope requirements for AC-BC concrete asphalt layers, the Optimum Asphalt Content (KAO) value in the most optimum AC-BC hot asphalt mixture of 7.30%. While the variation of HDPE addition 6%, 4% and glass powder 1%, 2%, 3% is most optimal at the addition rate of 2.5% and 0.5%. The determination is based on the Marshall test by combining the values of VIM, VMA, VFA, Stability, Flow and Marshall Quotient (MQ). Keyword: Asphalt, Additives, HDPE, Filler, KAO.